Cells nonproductively transformed by Abelson murine leukemia virus express a high molecular weight polyprotein containing structural and nonstructural components. - Reynolds, F H (1978)
Cell clones nonproductively transformed by the replication-defective Abelson strain of murine leukemia virus (AbLV) were analyzed for type C viral antigen expression by competition immunoassay. AbLV-transformed mink non-producer lines were found to express a 110,000- to 130,000-molecular weight polyprotein containing murine leukemia virus gag proteins p15 and p12 covalently linked to nonstructural AbLV-coded component(s) of around 80,000-100,000 molecular weight. This polyprotein lacked detectable antigenic cross-reactivity with other virion-coded gag gene proteins such as p30, p10, the viral reverse transcriptase (RNA-dependent DNA polymerase), or the major viral envelope glycoprotein, gp70. By analogy to earlier data on feline and avian sarcoma viruses, these results suggest that a portion of this polyprotein might represent the AbLV src gene product and that in translation it is initially linked in precursor form to gag structural proteins. Superinfection of mink cells nonproductively transformed by AbLV--with either a wild mouse amphotropic type C virus isolate, 4070-A, or with the endogenous cat virus, RD114--led to production of pseudotype virus containing high concentrations of the AbLV-coded precursor polyprotein.